Integrasi Nilai Ekonomi Syariah dalam Pengelolaan Dana BOS di Sekolah Islam - Sita Masirri Nurviani; Ulil Albab; Heri Sutopo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze how the integration of Islamic economic values operates in the management of School Operational Assistance (BOS) funds in Islamic schools and to identify supporting and inhibiting factors, as well as stakeholders’ perceptions regarding the application of sharia values in financial administrative practices. The research employs a qualitative descriptive approach using data reduction, data display, and conclusion drawing stages. The findings reveal that Islamic economic principles such as amanah (trustworthiness), sidq (honesty), al-‘adl (justice), and mas’uliyyah (accountability) have been internalized within the organizational culture and individual behavior of school managers, although not yet fully institutionalized. Supporting factors include religious leadership, Islamic ethical organizational culture, and community participation, while the main constraints involve limited human resources, low literacy in sharia accounting, and the absence of a faith-based monitoring system. Stakeholders demonstrate a strong moral awareness of sharia values but with limited technical understanding. The study concludes that effective integration requires synergy between spiritual values, technical capacity, and institutional policies to establish transparent and socially just financial governance in Islamic education institutions.